Cholangiocyte organoids can repair bile ducts after transplantation in the human liver. - Sampaziotis, Fotios; Muraro, Daniele; Tysoe, Olivia C; Sawiak, Stephen; Beach, Timothy E; Godfrey, Edmund M; Upponi, Sara S; Brevini, Teresa; Wesley, Brandon T; Garcia-Bernardo, Jose; Mahbubani, Krishnaa; Canu, Giovanni; et al. (American Association for the Advancement of Science (AAAS), 2021)
Organoid technology holds great promise for regenerative medicine but has not yet been applied to humans. We address this challenge using cholangiocyte organoids in the context of cholangiopathies, which represent a key reason for liver transplantation. Using single-cell RNA sequencing, we show that primary human cholangiocytes display transcriptional diversity that is lost in organoid culture. However, cholangiocyte organoids remain plastic and resume their in vivo signatures when transplanted back in the biliary tree. We then utilize a model of cell engraftment in human livers undergoing ex vivo normothermic perfusion to demonstrate that this property allows extrahepatic organoids to repair human intrahepatic ducts after transplantation. Our results provide proof of principle that cholangiocyte organoids can be used to repair human biliary epithelium.
Keywords: Animals; Bile; Bile Duct Diseases; Bile Ducts; Bile Ducts, Intrahepatic; Cell- and Tissue-Based Therapy; Common Bile Duct; Epithelial Cells; Gallbladder; Gene Expression Regulation; Humans; Liver; Liver Transplantation; Mesenchymal Stem Cell Transplantation; Mice; Organoids; RNA-Seq; Tissue and Organ Procurement; Transcriptome